Reasons for price rise at the real estate market in the Volgograd Region - N. M. Stepanenkova; A. L. Dubrovchenko (Вестник Северо-Кавказского федерального университета)
Introduction. In modern conditions, an important problem determining social stability is the rise in prices in the primary and secondary real estate markets, this trend is observed in all regions of the Russian Federation, including the Volgograd region.Goal. The purpose of the study is to assess the impact of a combination of factors on the cost of housing in the Volgograd region and identify possible directions for market development.Materials and methods. Structural and statistical analysis, as well as the synthesis of the results obtained, made it possible to form an objective assessment of the state of the real estate market in the Volgograd region.Results and discussion. The study obtained a result indicating the impact of government support measures in combination with pro-inflationary factors on stimulating the growth of housing demand with lagging rates of new housing commissioning and secondary market offers.Conclusion. Based on the results of the analysis, it can be concluded that the interaction of various economic factors contributed to a significant increase in prices in the real estate market. Nevertheless, an increase in the key rate, the demands of banks to increase the share of the down payment and a reduction in mortgage lending programs may cool demand in the primary housing market. The current slowdown in the pace of construction makes it impossible to significantly reduce prices, and therefore a convergence of prices in the primary and secondary markets is predicted.